(untitled) (Management and Connections Journal, 2023)
The present research aimed to understand how individuals belonging to generation Z seek to overcome the difficulties faced in the labor market and how their well-being is affected in this process. As a method, twelve in-depth interviews were carried out and the data collected were analyzed using the Content Analysis technique. Examining the results obtained, it was found that, given the difficulties faced in the job search process, the vast majority of interviewees dedicate themselves to continuing their studies to compensate for the lack of experience. It was also found that several of the interviewed, due to the need to earn some income during the period of unemployment, began to perform informal jobs, in areas totally different from their academic formation. Finally, it was concluded that, due to prolonged unemployment, the research subjects started to feel distressed, anxious and dissatisfied with their professional trajectory.